2019
DOI: 10.1108/bepam-11-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Communication performance challenges in PPP projects: cases of Ghana and South Africa

Abstract: Purpose The need to gain theoretical and practical understanding into the communication performance challenges in public private partnership (PPP) projects is considered as a precursor to effective communication strategies, management, planning and improvement in PPP models in both developed and developing countries. Hence, the purpose of this paper is to investigate the nature of communication performance challenges in PPP projects. Design/methodology/approach By adopting a deductive research design, a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…The study agrees with literature (Kwofie et al, 2019) that, to establish the role of PPPs in the implementation of the SDGs. The study recommends the scope of this study to be extended to other industries such as the mining and quarrying sector among others in the energy value chain.…”
Section: Conclusion and Recommendationssupporting
confidence: 91%
See 2 more Smart Citations
“…The study agrees with literature (Kwofie et al, 2019) that, to establish the role of PPPs in the implementation of the SDGs. The study recommends the scope of this study to be extended to other industries such as the mining and quarrying sector among others in the energy value chain.…”
Section: Conclusion and Recommendationssupporting
confidence: 91%
“…In Ghana, the PPP ideology began since the early 1990s, the private sector has been actively involved with public service delivery since (Agarchand and Laishram, 2017). However, the private sector's participation has mainly been the management of public service in the waste, energy, telecommunication and sanitation sectors (Kwofie et al, 2019). Hitherto, physical public infrastructures such as roads, railways, power plants, airports, bridges and public hospitals have private investors' participation been relatively low before the 1990s, but on a contrary, this is no more the case in recent times (Simshauser et al, 2016).…”
Section: Conception and Evolution Of Public-private Partnerships In Ghanamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the benefits from social PPPs is enhancing people's well-being by the early provision of new facilities [34]. To better achieve potential social PPPs benefits, improved communications among stakeholders is essential [35,36]. The mismatch between the contracts being managed remotely from the end-user makes integrated communication more difficult, particularly when the contracts focus on technical and economic concerns [37][38][39], risk analysis [40][41][42] and benefits as compared to traditional procurement [43,44].…”
Section: Service Quality Perceived By End-usermentioning
confidence: 99%
“…Furthermore, the authors employed a PPP transportation project to show the concession period determination process. Kwofie et al (2019) researched the nature of communication performance challenges in PPP projects. Using the deductive research design, the authors analysed the communication network of PPP projects in Ghana and South Africa and concluded that the communication challenges and information asymmetries are notable challenges.…”
Section: Introductionmentioning
confidence: 99%